PENGEMBANGAN VIDEO IKLAN MENGGUNAKAN APLIKASI VEGAS PRO UNTUK MENINGKATKAN MINAT BELI PADA UMKM GUD BITES BLITAR - Dondi Indra ’Asyam Januar; Tri Istining Wardani (CV. ADIBA AISHA AMIRA, 2024)
The purpose of this study was to use Vegas pro to create video ads as an additional promotional medium to increase purchasing interest in UMKM Gud Bites Blitar. The research method used is action research. Data collection methods included interviews, observations, and questionnaires. The questionnaire was distributed to 35 participants including 1 owner, 2 marketing experts, 2 computer experts and 30 potential consumers. The results of the questionnaire were analyzed using the EPIC model, AIDA, method and correlation coefficient to determine the relationship between variables, as well as a T-test to determine the partial influence of advertising on preferences. like to buy. Based on the results of advertising variable analysis, the EPIC ratio received a value of 3.84. This value proves that video ads are among the most effective. While the results of analyzing purchasing preferences with AIDA from April 21. This value is considered very effective. The correlation result between the advertising variable and the purchase interest variable gives a value of 0.811. Advertising variables partially influence purchasing preferences for UMKM Gud Bites Blitar